ANALISA KEMAMPUAN SERVIS PERMAINAN BOLA VOLI ANTARA TIM PUTRA-PUTRI PELAJAR INDONESIA DAN MALAYSIA PADA PERTANDINGAN ASEAN SCHOOL GAMES KE-11 TAHUN 2019 (Universitas Negeri Semarang, 2020)
The Indonesian and Malaysian women's teams always been in the semi-finals at the ASEAN School Games championships. Researchers were interested in knowing the skills of the service, which included 1) which positions are frequently attacked 2) what types of services are often used, and 3) more effectively which services are used. Research methods quantitative research with the subjects of Indonesian and Malaysian athletes who numbered 48 athletes in instrument research using observation methods. Data analysis techniques using descriptive percentages. Research results 1) the most frequently attacked position of the Indonesian and Malaysian teams position 6. 2) The types of services used by the Indonesian men's team are jump serve, Indonesian women's team floating serve, Malaysian men's team is jump floating serve, and Malaysian women's team jump floating serve. 3) The effectiveness of the service used in attacking on the most effective Indonesian men's team is a floating serve jump of 43.12 %, the Indonesian women's team jump serve 57.14%, the men's Malaysian team is a jump serve of 55.56%., and the Malaysian princess is a floating serve jump of 47.57%. Advice to Indonesian, Malaysian and bolavoli teams needs to train more varied service punches, and to train the accuracy of the service direction